Application of Biochar-Based Catalyst for The Upgrade of Pyrolysis Bio-Oil And Gas At A Wide Range Of Temperature - Mohamedelkhair, Ayman (2023)
A Master of Science thesis in Chemical Engineering by Ayman Mohamedelkhair entitled, “Application of Biochar-Based Catalyst for The Upgrade of Pyrolysis Bio-Oil And Gas At A Wide Range Of Temperature”, submitted in April 2023. Thesis advisor is Dr. Yassir Makkawi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).